A Case of Male Genital Psoriasis without Involvement of the Glans Penis - Nicolas Zubrzycki; Liang Joo Leow (Karger Publishers, 2022)
Genital psoriasis is a debilitating condition affecting approximately 49% of male psoriasis patients at least once during their lifetime. This condition often presents as generalized plaque psoriasis and features well-demarcated, erythematous plaques affecting the glans penis and corona. Presentations of male genital psoriasis which disagree with this description may be under- or misdiagnosed, delaying appropriate management. We present the first reported case of chronic plaque psoriasis affecting the penile shaft without involvement of the glans. Both consistent histologic and non-cutaneous features of psoriasis facilitated diagnosis in this patient. The sclerotic plaque on the patient's penile shaft resolved following biologic therapy for psoriasis. This rare presentation of genital psoriasis highlights important learning points for clinicians and dermatopathologists. First, genital psoriasis may affect the penile shaft without involvement of the glans penis. Second, non-cutaneous signs of psoriasis can inform diagnosis when clinical presentation is atypical. Third, psoriasis exhibits a broad spectrum of histopathology.